ROLE OF WOMEN IN AGRICULTURE IN NORTH INDIAN VILLAGES - Alok Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
Agriculture, which is the primary activity of the poor in many countries, has been identified as a key driver of economic expansion and poverty reduction by the community of people working in international development. 3 The agricultural and rural economies of all emerging nations are significantly bolstered by the contributions that women make. Their functions are very variable both across and within areas, and they are undergoing fast evolution in many parts of the world where economic and social pressures are causing the agricultural industry to undergo fundamental change. Women in rural areas frequently take on the responsibility of managing complicated homes and pursuing several sources of income. Producing agricultural crops, tending to animals, processing and preparing food, working for wages in agricultural or other rural enterprises, collecting fuel and water, engaging in trade and marketing, caring for family members and maintaining their homes are typical examples of the activities that they engage in. In national accounts, many of these activities do not meet the criteria for being considered "economically active employment," despite the fact that they are critical to the prosperity of rural households. This study makes a contribution to the ongoing discussion on gender issues in agriculture by evaluating the empirical data in three areas that have garnered a lot of interest in the existing research: